Overcoming Fungal Echinocandin Resistance through Inhibition of the Non-essential Stress Kinase Yck2. Issue 3 (19th March 2020) - Caplan, Tavia; Lorente-Macías, Álvaro; Stogios, Peter J.; Evdokimova, Elena; Hyde, Sabrina; Wellington, Melanie A.; Liston, Sean; Iyer, Kali R.; Puumala, Emily; Shekhar-Guturja, Tanvi; Robbins, Nicole; Savchenko, Alexei; et al.
Summary: New strategies are urgently needed to counter the threat to human health posed by drug-resistant fungi. To explore an as-yet unexploited target space for antifungals, we screened a library of protein kinase inhibitors for the ability to reverse resistance of the most common human fungal pathogen, Candida albicans, to caspofungin, a widely used antifungal. This screen identified multiple 2, 3-aryl-pyrazolopyridine scaffold compounds capable of restoring caspofungin sensitivity. Using chemical genomic, biochemical, and structural approaches, we established the target for our most potent compound as Yck2, a casein kinase 1 family member. Combination of this compound with caspofungin eradicated drug-resistant C. albicans infection while sparing co-cultured human cells. In mice, genetic depletion of YCK2 caused an ∼3-log10 decline in fungal burden in a model of systemic caspofungin-resistant C. albicans infection. Structural insights and our tool compound's profile in culture support targeting the Yck2 kinase function as a broadly active antifungal strategy. Graphical Abstract: Highlights: Screen of kinase inhibitors identifies Yck2 kinase as a promising antifungal target Clinical echinocandin resistance is reversed by pyrazolopyridine Yck2 inhibitors Combination treatment eradicates fungus while sparing co-cultured human cells Genetic depletion of YCK2 markedly impairs Candida albicans virulence in mice Abstract : New agents are needed to counter infection by drug-resistant fungi. We screened protein kinase inhibitors for the ability to reverse antifungal resistance. Chemogenomic, biochemical, and structural data established Yck2 as the target of our most potent hit. Findings support inhibiting this kinase as a promising therapeutic strategy.